A fault location method based on polarization analysis for coal mine - Zeng, Linfeng; Wang, Bo; Xin, Guoxu; Li, Yunchen; She, Zilong; Shen, Sihongren; Xie, Liujun (Frontiers in Earth Science, 2023)
A fault is a main cause for water inrush in coal mines. The detection of faults plays an important role in the prevention and governance of water inrush in coal mines. It is hard to determine the direction of seismic wave propagation under the condition of full space of mines, leading to difficulty in accurate fault detection. This paper compares and analyzes the polarization information extraction capability of time-domain polarization analysis (PA), frequency-domain polarization analysis, and time-frequency (TF)-domain polarization analysis, and proposes a TF-domain polarization analysis-based method for locating faults in coal mines. Firstly, the polarization analysis of signals mixed in the time domain was carried out. The results of three kinds of polarization analysis show that the TF-domain polarization analysis can accurately determine the polarization direction of multi-type signals in the case of aliasing. Secondly, a time-space-domain high-order three-dimensional three-component numerical simulation experiment was conducted. The TF-domain polarization analysis was adopted to extract the polarization information of each geophone and locate the fault. The error of the predicted fault strike was 0.16, and the distance deviation was lower than 2%. Finally, in-situ three-component seismic signals of coal mine were used to predict the location and strike of fault. The data from on-site actual drilling verified the effectiveness of the mine fault location method based on the TF-domain polarization analysis.